Arbitraje en fusiones y adquisiciones de empresas - García Long, Sergio (2017)
Arbitration is a mechanism to solve conflicts different to the judicial system. It characterizes for being private, flexible and specialized. For those reasons, arbitral clauses are preferred in diverse types of contracts, especially in commercial contracts.In this article, the author develops the application of contract clauses, originated on Common Law, on a Civil Law context, specifically on merger and acquisition contracts, and how they had been interpreted in arbitration in Peru. Also, the article analyzes which are the applicable rules of these American clauses on Peruvian law and which rules, imperative or not, must be considered while incorporating these clauses on the contract.